PENGARUH MODIFIKASI ATRAKTAN TERHADAP JUMLAH TELUR NYAMUK Aedes sp YANG TERPERANGKAP DI KELURAHAN KARANGPUCUNG KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS TAHUN 2014 - Sovi Milasari; Mela Firdaust (Poltekkes Kemenkes Semarang, 2015)
Millennium Development Goals (MDGs), which is about illuminating the sixth goal of HIV / AIDS,malaria and other infectious diseases. One infectious disease is a disease of Dengue Hemorrhagic Fever(DHF). The purpose of this study is to determine the effect of the modification attractant the number ofeggs of Aedes sp Karangpucung trapped in the Village, District of Purwokerto Selatan Banyumas2014.Pre-experimental research design is, this research design using the static group comparisondesign. Determining sampling at this research using inclusion criteria. 5 study subjects DHF casesin 2013 were located in the Village. Karangpucung. Data accumulation techniques is by usingquestionner. Data analysis using Kruskall Wallis test as an alternative to One Way Anova test.Kruskal-Wallis statistical test results obtained p = 0.007 ≤ α 0,05 mean there is a significantdifference between the number of eggs of Aedes sp trapped in each attractant. Then followedeach test group differences using nonparametric analysis with the U Mann Whitney testgroups 1 and 2 are significant (p = 0.631) meaning that there is no difference, groups 1 3 and 2 3groups was significant (p = 0.009) means there different.In conclusion, the effect of the modification there isattractant against Aedes sp Karangpucungtrapped in the Village District of Purwokerto Selatan Banyumas 2014. Suggestion submitted to thecommunity should play an active role in the activities PSN Plus 3M.